De Novo Construction of Catenanes with Dissymmetric Cages by Space‐Discriminative Post‐Assembly Modification. (9th March 2020) - Li, Pan; Xu, Shijun; Yu, Chunyang; Li, Zi‐Ying; Xu, Jianping; Li, Zi‐Mu; Zou, Lingyi; Leng, Xuebing; Gao, Shan; Liu, Zhiqiang; Liu, Xiaoyun; Zhang, Shaodong
Abstract: Considerable efforts have been made to increase the topological complexity of mechanically interlocked molecules over the years. Three‐dimensional catenated structures composed of two or several (usually symmetrical) cages are one representative example. However, owing to the lack of an efficient universal synthetic strategy, interlocked structures made up of dissymmetric cages are relatively rare. Since the space volume of the inner cavity of an interlocked structure is smaller than that outside it, we developed a novel synthetic approach with the voluminous reductant NaBH(OAc)3 that discriminates this space difference, and therefore selectively reduces the outer surface of a catenated dimer composed of two symmetric cages, thus yielding the corresponding catenane with dissymmetric cages. Insight into the template effect that facilitates the catenation of cages was provided by computational and experimental techniques. Abstract : Das Beste kommt danach : Catenane mit dissymetrischen Käfigen (CDCs) wurden durch Synthese von Imin‐basierten CSCs (Catenane mit symmetrischen Käfigen) und anschließende selektive Reduktion mit dem voluminösen Reduktionsmittel NaBH(OAc)3 hergestellt (siehe Bild). Der templatvermittelte Verzahnungsmechanismus für die Bildung dieser dreidimensionalen Catenane aus rein organischen Bestandteilen wurde aufgeklärt.